(untitled) (Revista Apotheke, 2022)
Since the modernist avant-gardes one can perceive the dissidence of the common ways of making art and the use of technology. Gradually, the creations abandon the traditional distinction between production and consumption, original and copy; it’s no longer a question of creating from raw material, but using objects that already have a configuration and that are in circulation in the cultural market for artistic creation. The arts become an editing island that subverts and makes different social formations, creative languages, affections and effects interact. Through reuse and recontextualization, multiple artistic productions can be composed using pre-existing configurations as a toolbox and which can confront life management strategies, bringing possibilities of political resistance through artistic and technological recombinations.